An integrated biomarker of PD‐L1 expression and intraepithelial CD8+ T cell infiltration was associated with the prognosis of lung cancer patients after intracranial resection of brain metastases. Issue 13 (20th May 2022) - Li, Lin‐Lin; Zhou, De‐Xiang; Lu, Ming; Zhou, Dong; Lin, Xiao‐Feng; Chen, Yu; Yin, Kai; Feng, Hui‐Bo; Guo, Wei‐Bang; Xie, Zhi; Yan, Wen‐Qing; Lv, Zhi‐Yi; et al.
Abstract: Background: Brain metastases (BM) are common in lung cancer. However, data on the status of immune biomarkers in BM lesions remain limited. Methods: We retrospectively analyzed PD‐L1 expression and infiltration levels of CD3 +, CD4 +, CD8 + T cells as biomarkers by immunohistochemistry in both BM lesions and primary lung cancer (PL) lesions of 29 lung cancer (LC) patients. In addition, the correlations between these biomarkers and the clinical outcome were analyzed using log‐rank test. Results: Intratumoral heterogeneous expression of PD‐L1 was observed on tumor cells (TCs) in 11 cases and on immune cells (ICs) in 10 cases with BM samples from multiple regions. There was a disagreement in PD‐L1 expression on TCs between paired BM and PL lesions in 15 cases and on ICs in seven cases. Intraepithelial CD3 + and CD8 + T cell infiltration levels in BM samples were lower than those in the paired PL samples. PD‐L1 positivity on both TCs and ICs was associated with a better post‐BM‐surgery prognosis ( p = 0.010; p = 0.041). Notably, PD‐L1 positivity on TCs and a high level of intraepithelial CD8 + T cell infiltration could serve as an integrated biomarker that indicates longer survival time ( p = 0.004) in LC patients. Conclusion: The heterogeneity in PD‐L1 expression was common in both stromal and intraepithelial regions in BM lesions of LC patients, suggesting the need for multiregional PD‐L1 testing in clinical practice. More importantly, a combination of PD‐L1 expression on TCs with intraepithelial CD8 + T cell infiltration might predict better post‐BM‐surgery outcomes. Abstract : Heterogeneity in PD‐L1 expression existed within each type of BM and PL lesions and between paired BM and PL lesions in lung cancer patients. A combination of PD‐L1 expression on tumor cells with intraepithelial CD8 + T cell infiltration may be an effective prognostic biomarker for lung cancer patients with BM.